Assessment of proportion of central incisor width in the maxilla to that in the mandible in natural and artificial teeth - Mohammadali Sadeghi; Reza Kodadadi; Shirin Geravand (Isfahan University of Medical Sciences, 2011)
Introduction: Selection of appropriately-sized central teeth has an important role in esthetics of dentures. The aim of this study was to compare proportion of mesiodistal width of central incisors in the maxilla to those in the mandible in students and products of Idealmako Company.Materials and Methods: In this descriptive-analytical study, 93 students of Isfahan Faculty of Dentistry in the age range of 20-30 were selected randomly. Mesiodistal widths of left and right upper and lower centrals were recorded by two methods: directly, using an intraoral caliper, and indirectly, using subjects' casts and a caliper with an accuracy of 0.01 mm at height of counter of the teeth three times. The sizes of Idealmako products were measured by the same caliper. Data was analyzed by one-way ANOVA, t-test and post hoc Scheffé's test using SPSS software (α = 0.05). Results: Proportion of upper-to-lower mesiodistal width of centrals was 1.55 ± 0.13 in students and 1.68 ± 0.17 in Idealmako products.Conclusion: Mean proportion of mesiodistal width of upper centrals to lower centrals in natural teeth is less than that in artificial teeth. A similarity between the width of upper centrals in the natural and artificial teeth (the numerator of the fraction) accounts for this significant difference between the proportion of the two groups, leading to the very small size of lower centrals (denominator of the fraction) in Idealmako artificial teeth. Key words: Artificial teeth, Dental esthetics.